Correction: Formation of plutonium(iv) silicate species in very alkaline reactive media. Issue 17 (6th April 2022) - Estevenon, Paul; Dumas, Thomas; Solari, Pier Lorenzo; Welcomme, Eleonore; Szenknect, Stephanie; Mesbah, Adel; Kvashnina, Kristina O.; Moisy, Philippe; Poinssot, Christophe; Dacheux, Nicolas
Abstract : Correction for 'Formation of plutonium(iv ) silicate species in very alkaline reactive media' by Paul Estevenon et al., Dalton Trans., 2021, 50, 12528–12536, DOI: ; 10.1039/D1DT02248B .